A Compliance With The Language Politeness Principles In The Virtual Lecture Context At The English Tadris Study Program Of The State Islamic Institute (IAIN) Sorong - Alif Hasanah; Siti Mujahidah Haris; Adelia Ardita (Universitas Negeri Makassar, 2022)
Abstract. This research discussed the implementation of language politeness principles in the virtual lecture context in the first semester at the English Tadris Study Program of the State Islamic Institute (IAIN) Sorong. This research objective was to examine speech acts of language politeness in the lecture process and to provide an overview of learning, teaching, and seeking independent information with the benchmark of language politeness principles. Thus, it can be seen the extent to which students and lecturers understand and apply the language politeness principles in the virtual lecture context in the first semester of the English Language Tadris Study Program of State Islamic Institute (IAIN) Sorong. This research used a qualitative approach as a methodological approach and a pragmatic study as a theoretical approach. The data collection technique in this research was the free-of-conversation listening technique, in which the researcher was not involved in the conversation. Researchers collected data by listening to lecture recordings or via the Zoom meeting application. The data was converted into written data. The results showed that in the lecture process, the interaction of lecturers and students complied with the six language politeness principles. The six principles included the tact maxim, modesty maxim, approbation maxim, agreement maxim, sympathy maxim, and generosity maxim. In addition, based on the conversations between lecturers and students, it appeared that the relationship between the two parties was harmonious, and no one felt dominated or dominated. Keywords: Students And Lecturers, Language Politeness Principles, And Speech Acts